Early Functional Status After Surgery for Congenital Heart Disease: A Single-Center Retrospective Study*. Issue 2 (February 2022) - Han, Brian; Yang, Jeffrey K.; Ling, Albee Y.; Ma, Michael; Kipps, Alaina K.; Shin, Andrew Y.; Beshish, Asaad G.
Abstract : OBJECTIVES: The objective of this study is to investigate the change in functional status in infants, children, and adolescents undergoing congenital heart surgery using the Functional Status Scale. DESIGN: A single-center retrospective study. SETTING: A 26-bed cardiac ICU in a free-standing university-affiliated tertiary children's hospital. PATIENTS: All patients 0–18 years who underwent congenital heart surgery from January 1, 2014, to December 31, 2017. INTERVENTIONS: None. MEASUREMENTS AND MIN RESULTS: The primary outcome variable was change in Functional Status Scale scores from admission to discharge. Additionally, two binary outcomes were derived from the primary outcome: new morbidity (change in Functional Status Scale ≥ 3) and unfavorable functional outcome (change in Functional Status Scale ≥ 5); their association with risk factors was assessed using modified Poisson regression. Out of 1, 398 eligible surgical encounters, 65 (4.6%) and 15 (1.0%) had evidence of new morbidity and unfavorable functional outcomes, respectively. Higher Surgeons Society of Thoracic and the European Association for Cardio-Thoracic Surgery score, single-ventricle physiology, and longer cardiopulmonary bypass time were associated with new morbidity. Longer hospital length of stay was associated with both new morbidity and unfavorable outcome. CONCLUSIONS: This study demonstrates the novel application of the Functional Status Scale on patients undergoing congenital heart surgery. New morbidity was noted in 4.6%, whereas unfavorable outcome in 1%. There was a small change in the total Functional Status Scale score that was largely attributed to changes in the feeding domain. Higher Society of Thoracic and the European Association for Cardio-Thoracic Surgery score, single-ventricle physiology, and longer cardiopulmonary bypass times were associated with new morbidity, whereas longer hospital length of stay was associated with both new morbidity and unfavorable outcome. Further studies with larger sample size will need to be done to confirm our findings and to better ascertain the utility of Functional Status Scale on this patient population.